Formation of Research Competences of Bachelors of Library and Information Activities - E. Yu. Kachanova (Высшее образование в России)
The article focuses on the increasing importance of research activities of libraries as a management tool and substantiates the necessity of the development of library specialists’ professional research competencies. The activities of modern libraries depend to a large extent on the external conditions and available resources. Librarians have to monitor the requirements of their founders and consumers, the priorities of cultural policy, staff resources, innovative potential and other factors. Library specialists therefore face new challenges. Today their activities acquire not only cultural meaning but also marketing, management and strategic dimensions. Researches and analytics enable to take into consideration changes and to adjust managerial decisions, to reveal opportunities and risks. Library research workers study reading preferences among the different social groups, their level of informational culture as well as their satisfaction with library services, the role of libraries in the structure of communication channels, the quality of library activities. In this connection, Khabarovsk State Institute of Culture has introduced in the curricular of students majoring in “Management of Library and Information Activities” disciplines “Sociological research in library and information science” and “Marketing research in library and information science”. Training has practice-oriented character, it means that every student performs his own research as a course project. The final qualification work is aimed at working out a development strategy for a particular library (a research base) taking into account specific situation. It is based on gathering data (sociological survey), and their interpretation using the research methods according to the adopted program. The program contains the description of the purpose, object, hypothesis, concept, survey frame, research methods, stages of the research. The results obtained and recommendations should be described in the report. During the implementation of the study students acquire the necessary research skills and professional competences in the sphere of library and information activities.